El mobbing y la satisfacción laboral, sindicato único de trabajadores del Municipio de Archidona, 2022 - Chicaiza Cuñas, Karen Jomayra (2023)
ABSTRACT: This research analyzed the Mobbing and Job Satisfaction of SUTMAR workers, Archidona, 2022. The analysis was carried out with a population of 120 workers, 23 women, and 87 men; the ages range from 22 to 60 years. The study was of a documentary and bibliographical type, transverse design with descriptive and correlational levels. The information was obtained through an observation guide that collected data from the psychological batteries applied to the workers, which the professionals of the Single Union of Workers of the Municipality of Archidona provided. The instruments were the LIPT-60 Workplace Harassment Strategies Questionnaire and the SL-ARG Job Satisfaction Scale. The results obtained indicated that 57.5% present a latent risk of Mobbing or workplace harassment and 25% of regular job satisfaction, these being the most relevant scores obtained. On the other hand, the existence of any Mobbing was found that 64.2% presents a latent risk of personal discredit and 94.2% of the possible danger of labor discredit—a correlation between the study variables. In the same way, it was possible to identify no correlation between Mobbing and Job satisfaction (r = -.098; p < .05). This indicated no relationship between the two variables. Therefore, the alternative hypothesis is rejected, and the null hypothesis is accepted. Mobbing was considered a cause that determines job satisfaction, not a unique consequence for job well-being. Based on the results obtained, a psychological therapeutic plan is presented to prevent and reduce the presence of Mobbing.